ANALISIS PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN (Studi pada Perumahan Sembungharjo Permai Pengembang PT. Sindur Graha Tama) - Wibowo, Ariadi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2009)
Product Quality in housing is qualified as low. This is indicated by complaints from the consumers to their developers. Data from YLKI (Yayasan Perlindungan Konsumen Indonesia/The Indonesian Consumers Foundation) shows that there are lots of complaints received from the housing consumers about the developers. There are also many housing consumers that sent their complaints in mass media. Based on these facts, this research tries to answer the problem of how to improve the consumers' satisfaction.To answer the problem, a conceptual model with three variables is being established. The variables are core product, extended product, and consumers' satisfaction. From the model, two hypotheses are formulated. To test the hypotheses, data is collected by conducting interviews to 138 respondents who are the owner of the house in the Housing of Sembungharjo Permai using questionnaires. Then, the data is analyzed with Multiple Regression Method.The test result under the multiple regression method shows that all the two hypotheses is statistically acceptable. It means that the housing consumers' satisfaction is affected by core product and extended product of the housing.